Register of Japanese Nursing (Kango/Kaigo) Language - et. al., Hardianto Rahardjo, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The concerning decline in Japanese population caused by the lower ratio of births compared to mortality, had caused an alarmingly increasing number of elders and low numbers of youngsters in Japan. Due to the lack of professional workforce in productive ages, Japan government had been forced to recruit foreign workforce to work in Japan. One of several countries who have been constantly supplying Japan with the much needed workforce is Indonesia. Every year, no less than 25.000 workforces has been sent to Japan, and the number hasn’t shown any sign of declining, even amidst the dangerous pandemic that struck both countries in the late 2 years. One of the specific skilled workforces that constantly in high demand is kaigo and kango, or medical nurses. Nevertheless, albeit being well trained in medical care, most of the candidates need to be trained to speak Japanese first, which would take more time and costs before they can be employed. One among several method to decrease the time and costs to train them Japaese is to provide a short but adequate crash course in Japanese conversation and etiquette.